"Watch Me!" A Testimonial to the Importance of Bearing Witness in Child Analysis. Issue 1 (1st January 2018) - Silver, Gabrielle; Gilmore, Karen
ABSTRACT: The supervision of a candidate's first child psychoanalysis is an opportunity to revisit, with the freshness of discovery, the infinitely varied representations of core childhood conflicts. Because the developmental process poses similar challenges at the interface of mental life and environment, most children must grapple with experiences of separation and loss, the impact of siblings, disruptions of their narcissistic balance, and enumerable moments of misattunement by their significant others, including the analyst. The idiosyncratic appearance of these conflicts and their complex relationship to ongoing developmental progression are specific and unique, but all children must struggle with them and all children need to be noticed and seen to feel recognized and securely held in mind.